2012
DOI: 10.20533/licej.2040.2589.2012.0113
|View full text |Cite
|
Sign up to set email alerts
|

School Placement Decisions in Luxembourg: Do Teachers Meet the Education Ministry’s Standards?

Abstract: In Luxembourg, the assignment of primary-school

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 10 publications
(12 reference statements)
0
19
0
1
Order By: Relevance
“…These tracks differ in the educational qualifications students can acquire and determine students' educational career (Contini & Scagni, 2011;Glock et al, 2012;Korpershoek et al, 2016). A substantial body of research (e.g., Driessen et al, 2008;Dutch Inspectorate of Education, 2018c;Klapproth et al, 2012;OECD, 2016;Pietsch & Stubbe, 2007) has reported that students' background characteristics, including their families' socio-economic status (SES), have an impact on students' allocation to specific secondary school tracks. To create equal opportunities for all students, it is important that students are allocated to the secondary school track that is most appropriate based on their abilities, regardless of their SES (Tieben & Wolbers, 2010).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…These tracks differ in the educational qualifications students can acquire and determine students' educational career (Contini & Scagni, 2011;Glock et al, 2012;Korpershoek et al, 2016). A substantial body of research (e.g., Driessen et al, 2008;Dutch Inspectorate of Education, 2018c;Klapproth et al, 2012;OECD, 2016;Pietsch & Stubbe, 2007) has reported that students' background characteristics, including their families' socio-economic status (SES), have an impact on students' allocation to specific secondary school tracks. To create equal opportunities for all students, it is important that students are allocated to the secondary school track that is most appropriate based on their abilities, regardless of their SES (Tieben & Wolbers, 2010).…”
mentioning
confidence: 99%
“…In some countries, such as Great Britain and Singapore, track recommendations are based on students' results on a standardized, multisubject school leavers' test (Boone & Van Houtte, 2013;Le M etais, 2003). In other countries, such as Belgium, Germany, Luxembourg, and France, track recommendations are based on teachers' expectations about the most optimal level of secondary education for students to develop and perform successfully (Boone & Van Houtte, 2013;De Boer et al, 2010;Glock et al, 2012;Klapproth et al, 2012;Le M etais, 2003;Timmermans et al, 2015). These expectations are teachers' inferences about students' potential achievement, usually based on teachers' judgements of students' current performance as well as other characteristics, such as their motivation or behaviour (Boone & Van Houtte, 2013;Feron et al, 2015;Klapproth et al, 2012;Riley & Ungerleider, 2012).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, American teachers evaluate Hispanic students less positively than IQ-matched White students (McCombs & Gay, 1988); provide top Black students less praise, less direct questions, and less feedback after mistakes than non-Black peers (Casteel, 1998; Ferguson, 2003), or provide different forms of feedback and praise for the same work (Harber, 1998); and discipline Black students more severely than White students for equivalent offenses (Horner, Fireman, & Wang, 2010; Okonofua & Eberhardt, 2015). In Europe, students’ ethnic minority status influences the judgments of preservice teachers (i.e., teachers in training) about student competence (Glock & Krolak-Schwerdt, 2013), and shapes decisions to place migrant students into lower track secondary schools, regardless of students’ prior academic achievement (Klapproth, Glock, Böhmer, Krolak-Schwerdt, & Martin, 2012). Similar results have been observed in India, where essays ostensibly belonging to lower caste students are graded approximately 10% lower than the same essays associated with high-caste students (Hanna & Linden, 2012).…”
mentioning
confidence: 99%